Analysis of the Implementation of the Royalty System for Song Playback in Coffee Shops Based on Copyright Law in Indonesia - Singgih Eko Cahyono; Ira Alia Maerani (UNISSULA Semarang, 2025)
Abstract. The development of technology and digitalization has had a significant impact on the dynamics of the creation and distribution of intellectual works, such as music, books, designs, and software. In today's creative economy, creative works not only have aesthetic and cultural value but also have high economic value, making them one of the main sources of income for creators. In this context, the royalty system is an important instrument to provide compensation for the use of works, especially for commercial purposes. The large population in Indonesia has led to a variety of activities among Indonesians, one of which is playing and performing music, whether the performers are musicians directly or indirectly. The definition of song/music is basically slightly different but interrelated. A song is a musical unit consisting of a series of consecutive notes, each song is determined by the length, shortness, and pitch of the notes, and the rhythm also provides certain variations to a song. The song/music itself is a unified work of creation. The definition of creation according to Article 1 paragraph 3 of Law Number 28 of 2014 concerning Copyright is every creative work in the fields of science, art, and literature produced by inspiration, ability, thought, imagination, dexterity, skill, or expertise expressed in a tangible form. The development of an increasingly modern era, driven by the rapid advancement of information technology in the era of globalization, has brought major changes in various aspects of business ranging from investment, industry, to product marketing methods. This change is also followed by Intellectual Property in this case that is used in the process of product manufacturing and marketing. In the present era, the influence of globalization has touched almost all aspects of life, including the social, economic, and cultural fields. One of the most noticeable impacts is on the products of human thought and creativity, such as various works in the fields of science, art, and literature. Advances in digital technology make these works, including songs and music, easily disseminated and accessible to the wider community in various parts of the world. Many creative works are then used without permission or even pirated. Therefore, a clear legal protection system is needed to safeguard the rights of creators, performers, and other related rights holders. This protection is crucial to ensure that creators receive the recognition and compensation they deserve for their work.